2017
DOI: 10.1186/s12893-017-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of pelvic fracture patterns, pelvic binder use and arterial angio-embolization with transfusion requirements and mortality rates; a 7-year retrospective cohort study

Abstract: BackgroundPelvic fractures are severe injuries with frequently associated multi-system trauma and a high mortality rate. The value of the pelvic fracture pattern for predicting transfusion requirements and mortality is not entirely clear. To address hemorrhage from pelvic injuries, the early application of pelvic binders is now recommended and arterial angio-embolization is widely used for controlling arterial bleeding. Our aim was to assess the association of the pelvic fracture pattern according to the Tile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…As reported by Lunsjo et al [17] and Agri et al [21], most deaths related to pelvic fracture were caused by associated injuries, not the pelvic fracture itself. In these patients, the most common cause of death was severe traumatic brain injury [17,21,22]. Therefore, to speci cally investigate the correlation of the fracture pattern and pelvic vascular injury severity with the outcome, patients with an AIS score higher than 2 for body regions other than the pelvis were excluded from the current study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As reported by Lunsjo et al [17] and Agri et al [21], most deaths related to pelvic fracture were caused by associated injuries, not the pelvic fracture itself. In these patients, the most common cause of death was severe traumatic brain injury [17,21,22]. Therefore, to speci cally investigate the correlation of the fracture pattern and pelvic vascular injury severity with the outcome, patients with an AIS score higher than 2 for body regions other than the pelvis were excluded from the current study.…”
Section: Discussionmentioning
confidence: 66%
“…Most exsanguinating patients could be stabilized by transarterial embolization shortly after initial resuscitation whenever indicated [20,25,27,28]. Another reason for the lack of mortality was that pelvic trauma patients with associated injuries that were con rmed to be the principal cause of death, such as severe brain injury, were not included in the current study [17,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The interobserver reliability of the Tile classification system has been previously described as low and insufficient for research purposes 48 . In a previous paper -using a different set of observers -on a cohort with all pelvic ring injuries admitted to our hospital, we obtained a different distribution of fracture types 49 . Although the present study included only patients treated in a physician-staffed prehospital setting, the interobserver variability may influence our results and limit their value.…”
Section: Discussionmentioning
confidence: 99%
“…Agri et al [32] reported that Tile C fractures are significantly associated with more blood transfusion and a higher rate of mortality as compared to Tile A or B fractures. Unstable fracture is really the most serious skeletal injury due to complexity and high-energy related to other anatomical injuries [33].…”
Section: Discussionmentioning
confidence: 99%